Electronic Cigarettes and Vaping: A New Challenge in Clinical Medicine and Public Health.A Literature Review - Dominic L. Palazzolo (Frontiers Media S.A., 2013)
Electronic cigarette (e-cigarette) use in the United States and worldwide is increasing. These devices closely mimic smoking of conventional cigarettes and can be used by consumers as a substitute for their smoking and nicotine addiction. Reasons for their popularity are that vendors of e-cigarettes have previously marketed their product as a safer alternative to conventional cigarettes, and as a possible smoking cessation tool. Rather than inhaling harmful smoke from burning tobacco, users of electronic cigarettes inhale a potentially less harmful vaporized mist primarily consisting of propylene glycol, nicotine, and water in a process referred to as vaping. Furthermore, the e-cigarette web pages are full of anecdotal claims from ex-smokers on how e-cigarettes helped them to give up traditional cigarettes in favor of these electronic devices. Government agencies and the medical community are skeptical, indicating that there is not enough empirically-derived evidence to substantiate such claims. While vaping e-cigarettes appear to do very little to abate nicotine addiction, and almost certainly carry unknown potential dangers, its supporters believe it is a safer alternative to smoking cigarettes. However, before e-cigarettes and vaping can be considered as a viable harm reduction clinical approach to smoking cessation, the medical community must first face the challenges e-cigarettes and vaping present to public health. For example, what should the primary medical focus be for a patient who has successfully transitioned from conventional cigarettes to e-cigarettes? Should it be to maintain smoking abstinence or should it be to quit vaping? Would it not be prudent for a patient who is unwilling to quit smoking or to give up nicotine to vape instead of smoke? Given these circumstances, how should medical care providers advise their patients? To effectively face these challenges, health care professionals need to become more familiar with the existing evidence-based